Radiation of Ultra-Wideband (UWB) Signals - Immoreev, I.J.; Sinyavin, A.N. (Радиофизика и радиоастрономия, 2002)
The radiation of short duration signals (or ultra-wideband – UWB signals) is significantly different from the long duration narrowband signals (see Table 1 below). Paper analyzed the processes in linear antennas and gives a physical interpretation these differences. В статье анализируются процессы в линейных антеннах. Излучение сигналов короткой длительности (или сверхширокополосных) существенно отличается от излучения сигналов большой длительности (узкополосных). Приводится физическая интерпретация этих различий. У статті аналізуються процеси у лінійних антенах. Випромінювання сигналів короткої тривалості (або надширокосмугових) суттєво відрізняється від випромінювання сигналів з великою тривалістю (вузькосмугових). Наводиться фізична інтерпретація цих відмінностей.